Traditional community inserted in the initial mining process (Research, Society and Development, 2022)
The objective of this work was to investigate the representation of the residents of the rural community Serra da Boa Esperança and surroundings, municipality of Ipaporanga - CE, regarding the effects of the installation and process of iron mining on natural resources. The research consisted of a case study with a qualitative-quantitative approach, based on the application of alternative methodologies, such as Research-Action-Participant, and with an increase in the use of Participatory Rural Diagnosis techniques, such as choosing priorities and unstructured interviews. A total of 102 people contributed to the survey, and the interviews were applied to 70 residents. In theory, the residents have little understanding of the mining activity process, as well as the class of ore extracted. However, they are unfavorable to the establishment of programs that disturb the natural resources present in the region. From the method of choosing priorities, it was observed that participants engaged in social movements have greater knowledge on the subject. It is believed that popular environmental education projects, structured by social movements, sensitize families to strengthen resistance against environmental exploitation, designating strategies to prevent the establishment of mega-enterprises in these territories.